THREE-DIMENSIONAL NUMERICAL MODELLING OF FIRE EXPOSED COMPOSITE SLABS WITH STEEL DECK - Piloto, Paulo A G; Balsa, Carlos; Ribeiro, Fernando; Santos, Lucas; Rigobello, Ronaldo; Kimura, Erica (MATTER: International Journal of Science and Technology, 2019)
Composite slabs with reinforced concrete and cold-formed profiled steel deck are very popular and reduce the building construction time. The steel deck acts as a permanent formwork to the concrete topping. Usually, the concrete is reinforced with individual rebars placed within the ribs for positive bending, and a steel mesh on the top for negative bending and to prevent concrete cracking. The fire rating of these building elements involves the analysis of different criteria, namely load bearing (R), integrity (E) and insulation (I). The integrity is easily verified, due to the construction method. The other two metrics require the development of experimental fire tests, the application of simplified calculation methods or the development of advanced calculation models. This investigation introduces 3-D numerical validation models for load bearing (R) and insulation (I) criteria. Parametric analyses are developed to investigate the effect of the load into the fire resistance (R) and critical temperature of the steel components (deck, rebar and mesh), as well as the effect of the concrete thickness on the fire resistance from the insulation standpoint (I). The advanced calculation model consists of a non-linear analysis for the thermal and structural behaviour. Both thermal and mechanical models consider perfect contact between materials. For the thermal model, an alternative model is used, with an air gap included between the steel deck and concrete topping to simulate debonding effects. For the mechanical model, the live load level changes from 1.0 kN/m2 to 21.0 kN/m2, and the dead load presents a constant value of 2.8 kN/m2. The fire resistance is determined according to standards, based on the maximum displacement or the rate of displacement. The critical temperature of each steel component decreases with the load level. A new proposal is presented for the critical temperature of each steel component and for the fire resistance according to the insulation criterion.